Regional oligodendrocytopathy and astrocytopathy precede myelin loss and blood–brain barrier disruption in a murine model of osmotic demyelination syndrome. Issue 3 (23rd November 2017) - Bouchat, Joanna; Couturier, Bruno; Marneffe, Catherine; Gankam‐Kengne, Fabrice; Balau, Benoît; De Swert, Kathleen; Brion, Jean‐Pierre; Poncelet, Luc; Gilloteaux, Jacques; Nicaise, Charles
Abstract: The osmotic demyelination syndrome (ODS) is a non‐primary inflammatory disorder of the central nervous system myelin that is often associated with a precipitous rise of serum sodium concentration. To investigate the physiopathology of ODS in vivo, we generated a novel murine model based on the abrupt correction of chronic hyponatremia. Accordingly, ODS mice developed impairments in brainstem auditory evoked potentials and in grip strength. At 24 hr post‐correction, oligodendrocyte markers (APC and Cx47) were downregulated, prior to any detectable demyelination. Oligodendrocytopathy was temporally and spatially correlated with the loss of astrocyte markers (ALDH1L1 and Cx43), and both with the brain areas that will develop demyelination. Oligodendrocytopathy and astrocytopathy were confirmed at the ultrastructural level and culminated with necroptotic cell death, as demonstrated by pMLKL immunoreactivity. At 48 hr post‐correction, ODS brains contained pathognomonic demyelinating lesions in the pons, mesencephalon, thalamus and cortical regions. These damages were accompanied by blood–brain barrier (BBB) leakages. Expression levels of IL‐1β, FasL, TNFRSF6 and LIF factors were significantly upregulated in the ODS lesions. Quiescent microglial cells type A acquired an activated type B morphology within 24 hr post‐correction, and reached type D at 48 hr. In conclusion, this murine model of ODS reproduces the CNS demyelination observed in human pathology and indicates ambiguous causes that is regional vulnerability of oligodendrocytes and astrocytes, while it discards BBB disruption as a primary cause of demyelination. This study also raises new queries about the glial heterogeneity in susceptible brain regions as well as about the early microglial activation associated with ODS. Main Points: Rapid correction of chronic severe hyponatremia in mouse leads to functional impairments mimicking those found in ODS patients. In this model, necroptosis drives glial cell death in specific brain regions, precipitating myelin loss and blood‐brain barrier disruption.